Host nest defence does not act as selective agent against plumage polymorphism in brood parasites - Honza, Marcel; Štětková, Gabriela; Požgayová, Milica; Samaš, Peter (Proceedings. Biological sciences, 2024)
Batesian mimicry in brood parasites is often viewed as an evolutionary strategy to mitigate host aggression. Female common cuckoos (Cuculus canorus) exhibit two morphs: the hawk-like grey and the rufous one, potentially maintained by apostatic selection. It was hypothesized that the grey morph's predator-like appearance deters host defences, while the rufous morph benefits from its rarity by evading host attention. Previous research predominantly utilized static cuckoo dummies, lacking insights into real-world interactions. We investigated the effectiveness of the cuckoo morphs in accessing great reed warbler (Acrocephalus arundinaceus) nests under natural conditions. Analysing video-recorded cuckoo attempts, we found no significant difference in nest-access success between the morphs. Both experienced a similar probability of physical attacks when hosts were present, and the rufous morph did not evade host detection more often compared with the grey morph. These results fail to support the assumptions of (a) Batesian mimicry, that hawk-like mimicry enhances nest access or reduces host aggression, and (b) apostatic selection, that the rarity of the rufous morph confers an advantage in successfully accessing the host nest. Future research should aim to identify stages in the cuckoo's life cycle or host interactions where colour polymorphism provides an evolutionary benefit.
Keywords: Animals; frontline nest defence; Feathers; Biological Mimicry; Female; Birds; biologická evoluce; Songbirds; ženské pohlaví; mimikry; zpěvní ptáci; pigmentace; ptáci; Pigmentation; agrese; cuckoo hawk-like mimicry; peří; Batesian mimicry; Aggression; brood parasitism; host aggression; hnízdění; negative frequency-dependent selection; zvířata; Biological Evolution; Nesting Behavior